Penal Endorsements In Administrative Contracts - العموري محمد; العيسى أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
General administrative penalties are among the penalties that have recently emerged to confront some crimes that are not worth facing with criminal penalties due to their low gravity and severity in the eyes of society. Punishment for violating some laws and regulations, which makes it an entity independent of all other forms of penalties.